Association of IL1 gene polymorphisms with chronic periodontitis in Brazilians - Trevilatto, Paula C.; de Souza Pardo, Ana Paula; Scarel-Caminaga, Raquel M. [UNESP]; de Brito, Rui B.; Alvim-Pereira, Fabiano; Alvim-Pereira, Claudia C.; Probst, Christian M.; Garlet, Gustavo P.; Sallum, Antonio W.; Line, Sergio R. P. (Pergamon-Elsevier B.V. Ltd, 2011)
Chronic periodontal disease (PD) is an infectious immune-inflammatory illness. Polymorphisms in IL1 genes play a role in inflammatory diseases through the modulation of cytokine levels.Objective: This study aimed to investigate the association between polymorphisms in the IL1 gene cluster and chronic periodontitis in a Brazilian population.Design: A sample of 113 subjects over 25 years (mean age 41.2) were grouped into: 44 healthy individuals, 31 subjects with moderate and 38 with severe periodontitis. DNA was obtained through a mouthwash and oral mucosa scraping. PCR-RFLP was used to identify the following polymorphisms: ILIA C - 889T (rs1800587), IL1B C - 511T (rs16944), IL1B C + 3954T (rs11436340), IL1RN intron 2 (rs2234663). Differences in the allele/genotype/haplotype frequencies were assessed by Chi-square test (p < 0.05). The risk associated with alleles, genotypes and haplotypes was calculated as odds ratio (OR) with 95% confidence intervals (CI).Results: Neither ILIA (C - 889T) nor IL1B (C + 3954T) polymorphisms was associated with chronic PD. Allele T for IL1B (C - 511T) only associated with PD in the group of blacks and mulattos. Moreover, genotype 2/2 for IL1RN (intron 2) was associated with severe PD.Conclusions: Genotype 2/2 of IL1RN for the whole Brazilian population and allele T of IL1B (C - 511T) in a subgroup of Afro-Americans and mulattos were suggested as putative risk indicators for chronic periodontitis. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Genetic susceptibility; IL-1 gene; Chronic periodontitis; Periodontal risk factor; Polymorphisms